United Way of Baroda: Enabling Charity by World’s Largest Dancing Festival - Ravichandran, N (Journal of Business and Management Research, 2024)
This article describes the context, content and management of a cultural festival organized by United Way of Baroda (UWB) an affiliate of United Way, a reputed charitable organization in the USA. This paper discusses the operational challenges associated in managing this cultural festival. The revenue surplus generated from the cultural festival is used to provide financial support to improve health, education, and empowerment of the needy population in the geographical area where UWB is located. We record our experience in conducting a management audit for this activity by (a) detailing the planning and execution of critical activities, (b) risk associated with critical resources, activities, and the processes and (c) opportunities for enhancing revenue. The possibility of scaling up this activity is also discussed.